Prevalence of thyroid dysfunction in chronic obstructive pulmonary disease patients in a tertiary care center in North India - Chaudhary, Shyam Chand (J Family Med Prim Care, 2018)
INTRODUCTION: Thyroid dysfunction can cause inspiratory and expiratory muscle weakness in patients with or without chronic obstructive pulmonary disease (COPD) Thyroid dysfunction in COPD results in increased frequency of exacerbation thus lead to poor quality of life. It may further increase cardiovascular disease risk thereby increasing mortality. AIMS AND OBJECTIVES: This study was conducted to evaluate the prevalence of thyroid dysfunction and hence that the quality of life of COPD can be improved MATERIALS AND METHODS: This is a cross-sectional – prevalence study. The study was conducted over a period of 1 year from August 2015 to July 2016. The study group was consists of male and female COPD patients diagnosed with spirometry and severity was determined according to the global initiative for chronic obstructive lung disease classification criteria. The patients were enrolled in this study from medicine outpatient department (OPD), respiratory OPD and those admitted to indoor wards of Medicine Department. Patients were screened for thyroid dysfunction. RESULTS: Out of 171 patients, thyroid dysfunction was present in 43 patients. All of them were hypothyroid. The prevalence of thyroid dysfunction was 25%. In Stage A it was 20.5%, Stage B 25.7%, Stage C 23.4%, and in Stage D 30.4%. Thyroid dysfunction was associated with more frequent exacerbation. CONCLUSION: Thyroid dysfunction is a common extrapulmonary manifestation in COPD patients. It is associated with frequent exacerbations which affect the quality of life in these patients. Early detection and proper management can improve the quality of life in these patients.